KELAYAKAN USAHATANI PADI DAN JAGUNG DENGAN IRIGASI POMPA DI DESA NGEPOSARI KECAMATAN SEMANU - Ahmad Mustofa (FP AGRI 16 UMY 036, 2016)
THE FEASIBILITY OF RICE AND CORN FARMING WITH PUMP IRRIGATION AT NGEPOSARI VILLAGE, SEMANU SUBDISTRICT. This study aims to determine the use of farm input, revenue, profit, and the feasibility of rice and corn farming with pump irrigation at Ngeposari Village, Semanu, Gunung Kidul. This research is using non-proportional purposive sampling method involving 60 farmer respondents. Data is analyzed with four indicators of feasibility analysis RC ratio, land productivity, capital productivity and labor productivity . The result shows that labor cost and irrigation cost are the highest farm input costs. The average usage of farm input in rice and corn farmingwith wells pump irrigation is higher than corn farming with DAS irrigation. Except indicators of labor productivity , the value of the feasibility of corn farming with irrigation pump is the smallest. The value of labor productivity in corn farming with DAS and wells pumps were not significantly different . Therefore , it can be concluded that farming with wells and DAS pump irrigation systems are profitable and viable .